Workshop Report : Global Market Integration and the Sector Agri-Food Sector - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
Workshop on Global Market Integration and the Sector Agri-Food Sector (Suriname) 18-20 Nov 1998